2022
DOI: 10.1021/acssensors.1c01972
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Group A Streptococcal Disease via Solid-State Nanopore Detection of PCR Amplicons

Abstract: Single molecule detection methods are becoming increasingly important for diagnostic applications. Practical Early detection of disease requires sensitivity down to the level of single copies of the targeted biomarkers. Of the candidate technologies that can address this need, solid-state nanopores show great promise as digital sensors for single-molecule detection. Here, we present work detailing the use of solid-state nanopores as downstream sensors for a PCR-based assay targeting group A streptococcus (stre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…In the negative control experiment, several block events appeared in the current trace ( Figure 1 B, top). Scatter plots showed that these blocking events had blocking degrees within a range of 0.2–0.96 ( Figure 1 C), similar to the results reported by King’s group [ 23 ]. The PCR mixture contained replicase, bovine serum albumin, and other molecules, and these molecules produced translocation signals in the nanopore assay.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In the negative control experiment, several block events appeared in the current trace ( Figure 1 B, top). Scatter plots showed that these blocking events had blocking degrees within a range of 0.2–0.96 ( Figure 1 C), similar to the results reported by King’s group [ 23 ]. The PCR mixture contained replicase, bovine serum albumin, and other molecules, and these molecules produced translocation signals in the nanopore assay.…”
Section: Resultssupporting
confidence: 88%
“…Considering that PCR is widely used to amplify DNA, the combination of PCR and a nanopore sensor could greatly expand the application range of nanopore technology. Recently, SiNx solid-state nanopores with a diameter >5 nm have been used as downstream sensors for PCR products, and clinical samples of group A Streptococcus have been successfully identified [ 23 ]. However, it remains challenging to distinguish the blocking current signals of PCR products from those generated by the molecules in PCR buffer.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] In the past few years, several works have proven that the nanopore counter has a strong ability to determine DNA duplexes at a pico-mole level concentration. 26,28,29 Inspired by this, simple and sensitive sensing strategies for bacteria, 30 oligonucleotides, 20 and ions 31 based on combining the nanopore counting of DNA duplex and nucleic acid amplification approaches, such as loop-mediated isothermal amplification (LAMP), 32 Clustered Regularly Interspaced Short Palindromic Repeats/Cas (CRISPR/Cas) products, 33 and hybridization chain reaction (HCR), 34 have been developed. However, the length of dsDNA products by such methods was unfixed, which may lead to a broad distribution of the peak amplitudes of blockage currents and increase the difficulty in data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As such, this model system is representative of many nanopore sensing schemes currently in use in the field, and the analysis challenges we discuss are readily applicable to other, similar systems. 18,26,39 In this paper we describe a process to analyze the nanopore signals of structured polymers and introduce refinements of this basic approach to better realize our goal of separating events from mixed samples. This process is centred around the use of Nanolyzer, a graphical analysis tool provided by Northern Nanopore Instruments for nanopore event fitting, segmentation, and event substructure analysis.…”
Section: Introductionmentioning
confidence: 99%